Haemodynamic stability and incidence of adverse events during tracheal intubation without neuromuscular blockade: comparison of clinical versus bispectral-index monitored depth of anaesthesia - Aliyu, Husseina A.; Usman, Yohanna M.; Kpalap, Precious B.; Shaki, Rimamkanati; Malau, Thomas K.; Nuhu, Samuel I.; Embu, Henry Y.; Isamade, Erdoo S. (International Journal of Research in Medical Sciences, 2025)
Background: Haemodynamic stability during intubation is influenced by sympathetic response to laryngoscopy and intubation. Furthermore, the incidence of adverse events during intubation without NMB warrants further investigation. BIS-guided anaesthesia has been associated with improved haemodynamic outcomes compared to clinical monitoring alone. Despite these advantages, the utility of BIS monitoring during intubation without NMB remains underexplored. Methods: This was a randomised, single-blind, controlled clinical study conducted in the Jos university teaching hospital, Jos, Nigeria, among 56 children aged 2 to 6 years with ASA I and II scheduled for adenotonsillectomy. Patients were randomised into two groups, B and C, with patients in group B receiving BIS monitoring while those in group C received clinical monitoring for the depth of anaesthesia with sevoflurane and without a neuromuscular blocking agent. Haemodynamic changes and adverse events associated with laryngoscopy were noted. Data was analysed using SPSS with students’ t test and chi-square test being the statistical tests utilised, and the level of significance set at p=0.05. Results: Systolic blood pressures were slightly higher in group C than group B. Diastolic blood pressures were slightly higher in group B than group C, while differences in mean arterial pressure between group B and group C were not statistically significant (p=0.10). Adverse events were only found in group C, with 10.7% of patients developing laryngospasm. Conclusions: The monitoring of inhalational induction using clinical signs is an acceptable alternative to BIS and can be used in the absence of BIS.